New electrocardiographic criteria for the differentiation between counterclockwise and clockwise atrial flutter: correlation with electrophysiological study and radiofrequency catheter ablation. Issue 1 (1st July 1998) - Lai, L P; Lin, J L; Lin, L J; Chen, W J; Ho, Y L; Tseng, Y Z; Chen, C H; Lee, Y T; Lien, W P; Huang, S K S
Abstract : Objective: To develop new electrocardiographic (ECG) criteria for the differentiation between counterclockwise and clockwise atrial flutters. Background: Traditionally, the ECG differentiation between counterclockwise and clockwise atrial flutters is based on the flutter wave polarity in the inferior leads. However, determination of flutter wave polarity is subjective and sometimes difficult, especially in flutter waves of undulating pattern. Patients: The study comprised 37 consecutive patients with drug resistant atrial flutter; 30 had counterclockwise and 17 had clockwise atrial flutter (10 had both forms of atrial flutter). The isthmus dependence was confirmed by entrainment study and catheter ablation. The ECG patterns of both types of atrial flutter were compared and the flutter wave polarity in the inferior leads was determined by four independent cardiologists. Results: The flutter wave polarity in the inferior leads appeared negative in 24, positive in one, and equivocal in five of the counterclockwise atrial flutters; polarity appeared negative in one, positive in 10, and equivocal in six of the clockwise atrial flutters. However, the aVF/lead I flutter wave amplitude ratio was > 2.5 in all counterclockwise but < 2.5 in all clockwise atrial flutters. The flutter wave nadirs in the inferior leads corresponded to the upstrokes in V1 in all counterclockwise atrial flutters, but corresponded to the downstrokes in V1 in all clockwise atrial flutters. Conclusions: The flutter wave polarity in the inferior leads does not correlate well with the flutter wave rotating direction. However, counterclockwise and clockwise atrial flutters can be differentiated by new ECG criteria with high accuracy.